Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan CSR Sebagai Moderating Variable Pada Perusahaan Manufaktur di BEI - Mipo Mipo (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to analyze factors that influence company value and then to test the influence of corporate social responsibility on company value. The variables examined in this study are independent variable consisted of profitability, leverage, and company size. The dependent variables that used are company value and corporate social responsibility as a moderating variable.The population that used in this research is the manufacturing industries listed in 2016-2020 consisted of 143 companies. This study has 23 companies as sample that chosen based on the purposive sampling method. Data analysis technique used is multiple linear regression analysis using SPSS v25 application.The results of this study indicate that partially profitability had a significant positive effect on company value. Meanwhile, leverage and company size had no effect on company value. On the other side partially corporate social responsibility had a significant positive effect on company value. As moderating variable corporate social responsibility could moderate correlation of leverage with company value. While the correlation of variables profitability and company size could not.The conclusion of this researh is partially profitability and corporate social responsibility had significant positive effect on company value. While the variables of leverage and company size did not. And then corporate social responsibility could moderate correlation of leverage with company value. While the correlation of variables profitability and company size could not.